USING THE SELF-ASSEMBLY TECHNIQUE FOR THE FABRICATION OF ULTRA-THIN FILMS OF A PROTEIN - Borato,C.E. (1997)
The self-assembly technique is employed for producing alternating ultra-thin films of lysozyme and poly(styrene sulfonate) (PSS). The influence of important parameters in the self-assembly process, namely immersion time, drying method, solution pH and ionic strength, on adsorption kinetics is investigated by ultraviolet (UV) spectroscopy. The absorbance increases rapidly in the initial stages of adsorption for all pHs studied, before reaching a plateau indicative of complete adsorption. Adsorption is considerably more effective when the proton concentration in the solution increases, which is attributed to the increase in the positive charge density within the protein molecules. Furthermore, UV absorbance increases linearly with the number of bilayers (lysozyme/PSS), indicating that a constant amount of material is being adsorbed at each deposition process. These results are highly promising as the self-assembled films are of great interest for biotechnology and molecular electronic applications